A novel near-infrared fluorescence imaging probe that preferentially binds to cannabinoid receptors CB2R over CB1R. (July 2015) - Ling, Xiaoxi; Zhang, Shaojuan; Shao, Pin; Li, Weixia; Yang, Ling; Ding, Ying; Xu, Cong; Stella, Nephi; Bai, Mingfeng
Abstract: The type 2 cannabinoid receptors (CB2 R) have gained much attention recently due to their important regulatory role in a host of pathophysiological processes. However, the exact biological function of CB2 R and how this function might change depending on disease progression remains unclear and could be better studied with highly sensitive and selective imaging tools for identifying the receptors. Here we report the first near infrared fluorescence imaging probe (NIR760-XLP6 ) that binds preferentially to CB2 R over the type 1 cannabinoid receptors (CB1 R). The selectivity of the probe was demonstrated by fluorescence microscopy using DBT-CB2 and DBT-CB1 cells. Furthermore, in mouse tumor models, NIR760-XLP6 showed significantly higher uptake in DBT-CB2 than that in DBT-CB1 tumors. These findings indicate thatNIR760-XLP6 is a promising imaging tool for the study of CB2 R regulation.